PENANAMAN KARAKTER SPIRITUAL SEJAK DINI PADA ANAK USIA DINI DI PAUD, TK, SD PONPES RAUDLATUL ULUM CAMPUREJO BOJONEGORO - Choiri, Moh. Miftahul; Nurdiansyah, Denny; Rokhim, Auliyaur (ABIDUMASY, 2024)
This dedication is the author's effort to invite re-examination of the importance of character cultivation in early childhood. Lately, the spotlight on morals is quite serious, in other words, the quality of morals is still far from expectations. The quality of morals must always be strived for to be even better. School as an educational environment is a solid foundation in the process of character building. Character building requires early habituation because character cannot be formed in a short time. The role of education, especially school education, will greatly help in the formation of the main person. The school is one of the institutions responsible for the implementation of education that determines the success or failure of children's education. Therefore, teachers in Islam have the obligation to provide education and guidance to their children as a mandate from Allah SWT. The implementation method chosen is Participatory Action Research.  The PAR method is a service method that requires community participation and action as the main actors in the preparation and implementation of the program. Meanwhile, the researcher is a facilitator who helps students or service subjects so that they can develop and implement the program optimally until it is successful.